Pregnancy outcomes after transvaginal sacrospinous hysteropexy. (September 2017) - Cavkaytar, Sabri; Kokanalı, Mahmut Kuntay; Tasdemir, Umit; Doganay, Melike; Aksakal, Orhan
Abstract: Aim: To evaluate the pregnancy outcomes in women who underwent transvaginal sacrospinous hysteropexy with the review of the literature Study design: 54 women who underwent transvaginal sacrospinous hysteropexy due to ≥grade 2 uterine prolapse during six-year period were identified from a computer based database. 8 of these who had pregnancy resulted in live birth subsequent to transvaginal sacrospinous hysteropexy were enrolled in this study. They were examined in case of pelvic organ prolapse recurrence and were questioned about their current self satisfaction status and PISQ-12 questionnaire. Results: The median age of women was 36 years (range 29–43 years). All of the women were multiparous and there were no women with a previous cesarean section. All of the subsequent conceptions following operation occured spontaneously. The median time between hysteropexy and conception was 16 months (range 10–30 months). The pregnancies continued at least 37 weeks with only one preterm delivery (due to twin pregnancy). All 8 pregnancies were delivered by cesarean section. The median follow-up period after cesarean section was 45 months (range 7–60 months). Majority of women (7/8, 87.5%) were satisfied with current outcomes of sacrospinous hysteropexy and PISQ12 questionnaire scores revealed improvement in 87.5% (7/8) of women. Conclusion: Transvaginal sacrospinous hysteropexy is an appropriate surgical treatment method for symptomatic uterovaginal descensus in women who wish to preserve their uterine and future childbearing. And cesarean section is a reliable and satisfactory delivery route for women who underwent transvaginal sacrospinous hysteropexy.